Development of satellite telecommunications during the period 1990-2005 - Kumar, D. (Cranfield University, 1993)
The global telecommunications market is in the midst of a radical restructuring program. This is driven by the desire of governments to increase competition in existing markets and of companies to diversify their service product portfolio. These changes are taking place as a result of advances in technology as well as three powerful and interconnected forces – privatisation, globalisation and liberalisation. Introduction of new technologies in the form of Integrated Services Digital Networks ((ISDNs)and sophisticated integrated terminal equipment has resulted in the transformation of the telecommunications services market from mainly a single service industry limited by technology constraints into a multi-service industry limited by applications. As a result of privatisation and globalisation, the former national telecommunications carriers are beginning to expand overseas in order to grow. In regions where the market regulations have been liberalised, the changes have effectively shattered the highly protected and monopolistic national markets. These changes when incorporated into the present satellite communications industry indicate a shift in traffic structure as well as in the global satellite market structure.